2017
DOI: 10.3389/fonc.2017.00072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Treatment Options in Recurrent and/or Metastatic Squamous Cell Carcinoma of the Head and Neck

Abstract: The major development of the past decade in the first-line treatment of recurrent and/or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN) was the introduction of cetuximab in combination with platinum plus 5-fluorouracil chemotherapy (CT), followed by maintenance cetuximab (the “EXTREME” regimen). This regimen is supported by a phase 3 randomized trial and subsequent observational studies, and it confers well-documented survival benefits, with median survival ranging between approximately 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 88 publications
1
100
0
6
Order By: Relevance
“…In the treatment of recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC), Vermorken et al reported in 2008 that the EXTREME regimen prolonged OS when given as first‐line treatment for R/M HNSCC . Although there is a worldwide effort to prolong survival for such patients, the regimen remains the standard for R/M HNSCC . Predictive biomarkers for the efficacy of cetuximab regimens in head and neck cancer are thus needed to improve both the therapeutic index and cost‐effectiveness, as well as to increase our understanding of resistance pathways to aid future drug development.…”
Section: Introductionmentioning
confidence: 99%
“…In the treatment of recurrent/metastatic (R/M) head and neck squamous cell carcinoma (HNSCC), Vermorken et al reported in 2008 that the EXTREME regimen prolonged OS when given as first‐line treatment for R/M HNSCC . Although there is a worldwide effort to prolong survival for such patients, the regimen remains the standard for R/M HNSCC . Predictive biomarkers for the efficacy of cetuximab regimens in head and neck cancer are thus needed to improve both the therapeutic index and cost‐effectiveness, as well as to increase our understanding of resistance pathways to aid future drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum-based chemoradiation is the standard treatment for patients with locoregionally advanced, recurrent and/or metastatic HNSCC. Possibly, the major development in first-line treatment for these cases in the past decade was the introduction of cetuximab-a monoclonal antibody which binds to the extracellular domain of the human epidermal growth factor receptor-in combination with platinum chemotherapy [16]. Despite the reported improvements in survival and life quality, the cost-effectiveness of the introduction of cetuximab in developing countries, including Brazil, is mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors of distant metastasis for head and neck SCC (HN-SCC) are related to age, the site of the primary cancer, local and/or regional extension, and histologic grading (15). Patients with localized HN-SCC are treated with potentially curative therapy using treatment modalities that include surgery, radiotherapy, chemotherapy, and biologic therapy (16). The recurrence rate in early-stage HN-SCC ranges from 10% to 20%, and the recurrence rate in locally advanced HN-SCC exceeds 50%.…”
Section: Introductionmentioning
confidence: 99%